Power infrastructure in India: The issues and the strategies - Singh, Rajendra (2001)
The dismal figure of per capita power consumption in the country is an ample reflection on the state of power sector in India. Abundance of resources for thermal and hydro-electric projects as well as large pool of highly skilled manpower are available to wipe out the power deficit. The article lists a number of measures to achieve this objective like, choosing right generation technology for power generation, efficient renovation and maintenance, and effective plugging of transmission and distribution losses. - Reproduced
Keywords: India - Power industries; Power industry